The Real Crisis Waiting for the World: Oil Problem and Energy Security - Ozturk, Serdar; Sozdemir, Ali; Ulger, Ozlem (International Journal of Energy Economics and Policy, 2013)
It can be said that the global crisis in the world in 2008 deeply affected all states and changed almost all balances. Such crises experienced in the world during this period and possible same crises in the future are important. However, such crises have monetary solutions although they have resulted in serious destruction of economic and social structures of the countries. Nevertheless, if the necessary measures are not taken, a more serious crisis will arise in a future not too far from now. The difference of this crisis that will arise compared to the former ones is that there won’t be a monetary solution for it. Continuous growth in the increase of energy consumption in the world is an inevitable problem. This situation makes many countries around the world face the problem of energy independence and energy security. In this study, the classification and characteristics of energy sources will be discussed first. Then, energy independence and security problem created by termination of energy sources and their being under control of specific countries will be examined by comparative analysis method based on statistical data. Keywords: Energy Security; Oil Problem; Energy Crisis; Real Crisis; Energy Policy JEL Classifications: Q42; Q43; Q48